WD2014: Timescale for WAIS Divide Core 2006 A (WDC-06A) - Fudge, T. J. (IEDA: US Antarctic Program Data Center, 2017)
The West Antarctic Ice Sheet Divide (WAIS Divide, WD) ice core is a newly drilled, high-accumulation deep ice core that provides Antarctic climate records of the past ~68 ka at unprecedented temporal resolution. The upper 2850 m (back to 31.2 ka BP) have been dated using annual-layer counting. Here we present a chronology for the deep part of the core (67.8-31.2 ka BP), which is based on stratigraphic matching to annual-layer-counted Greenland ice cores using globally well-mixed atmospheric methane. We calculate the WD gas age-ice age difference (Delta age) using a combination of firn densification modeling, ice-flow modeling, and a data set of d15N-N2, a proxy for past firn column thickness. The largest Delta age at WD occurs during the Last Glacial Maximum, and is 525 +/- 120 years. Internally consistent solutions can be found only when assuming little to no influence of impurity content on densification rates, contrary to a recently proposed hypothesis. We synchronize the WD chronology to a linearly scaled version of the layer-counted Greenland Ice Core Chronology (GICC05), which brings the age of Dansgaard-Oeschger (DO) events into agreement with the U/Th absolutely dated Hulu Cave speleothem record. The small Delta age at WD provides valuable opportunities to investigate the timing of atmospheric greenhouse gas variations relative to Antarctic climate, as well as the interhemispheric phasing of the \\"bipolar seesaw\\". We present the WD2014 chronology for the upper part (0-2850 m; 31.2 ka BP) of the West Antarctic Ice Sheet (WAIS) Divide (WD) ice core. The chronology is based on counting of annual layers observed in the chemical, dust and electrical conductivity records. These layers are caused by seasonal changes in the source, transport, and deposition of aerosols. The measurements were interpreted manually and with the aid of two automated methods. We validated the chronology by comparing to two high-accuracy, absolutely dated chronologies. For the Holocene, the cosmogenic isotope records of 10Be from WAIS Divide and 14C for IntCal13 demonstrated that WD2014 was consistently accurate to better than 0.5% of the age. For the glacial period, comparisons to the Hulu Cave chronology demonstrated that WD2014 had an accuracy of better than 1% of the age at three abrupt climate change events between 27 and 31ka. WD2014 has consistently younger ages than Greenland ice core chronologies during most of the Holocene. For the Younger Dryas-Preboreal transition (11.595 ka; 24 years younger) and the Bolling-Allerod Warming (14.621 ka; 7 years younger), WD2014 ages are within the combined uncertainties of the timescales. Given its high accuracy, WD2014 can become a reference chronology for the Southern Hemisphere, with synchronization to other chronologies feasible using high-quality proxies of volcanism, solar activity, atmospheric mineral dust, and atmospheric methane concentrations.